Comparison of chemotherapy response and adverse effects of double-platinum plus egfr-tki versus double-platinum alone on nslclc patients with disease progression and egfr-tki treatment - Wulandari, Laksmi; Wiriansya, Edward Pandu (Folia Medica Indonesiana, 2017)
EGFR-TKI is the first-line therapy for EGFR-mutant patients. Nevertheless, patients will have disease progression (median PFS 10 – 12 months) due to resistance. The treatment options are still limited in developing countries for such cases, thus double-platinum chemotherapy is the next option. Although IMPRESS study reported no difference in terms of PFS and OS between double-platinum alone and double-platinum plus EGFR-TKI, several local studies reported benefit of continuing EGFR-TKI in combination with double-platinum chemotherapy (treatment beyond progression). This study aimed to compare chemotherapy effects of double-platinum plus EGFR-TKI versus double-platinum alone on patients with NSCLC progression after EGFR-TKI treatment. This was an analytical descriptive study using prospective cohort design, involving 30 patients with disease progression following EGFR-TKI treatment that met inclusion criteria in Dr. Soetomo Hospital. Subjects were divided into two groups: arm A (double-platinum plus EGFR-TKI) and arm B (double-platinum alone). Subjects were observed until 4 cycles of double-platinum chemotherapy. Subjective response (body weight and EQ5D questionnaire) was analyzed, chest CT scans were evaluated using RECIST criteria, and adverse effects were monitored. This study was conducted in accordance with GCP principles and has received ethics certificate from Dr. Soetomo Hospital ethics committee (No. 08/Panke.KKE/I/2017). The results showed that subject characteristics between two arms were insignificantly different (p=0.05). The most common EGFR mutation was exon 21 (50% on arm A and 60% on arm B). Chi square was tested on subjective response parameter (EQ5D (p=0.483)). T2 free sample was tested on semi-subjective parameter (body weight (p=1.00)). Comparison test on both groups after cycle 2 and 4 showed p value=0.05. Statistical test on adverse effect between both groups showed p value=0.526. As a conclusion, there was no significant difference between double-platinum and double-platinum plus EGFR-TKI on patients who had disease progression following EGFR-TKI treatment.